Electrophoretic Mobility of DNA in Solutions of High Ionic Strength - Stellwagen, Earle (Biophys J, 2020)
The free-solution mobilities of small single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA) have been measured by capillary electrophoresis in solutions containing 0.01–1.0 M sodium acetate. The mobility of dsDNA is greater than that of ssDNA at all ionic strengths because of the greater charge density of dsDNA. The mobilities of both ssDNA and dsDNA decrease with increasing ionic strength until approaching plateau values at ionic strengths greater than ∼0.6 M. Hence, ssDNA and dsDNA appear to interact in a similar manner with the ions in the background electrolyte. For dsDNA, the mobilities predicted by the Manning electrophoresis equation are reasonably close to the observed mobilities, using no adjustable parameters, if the average distance between phosphate residues (the b parameter) is taken to be 1.7 Å. For ssDNA, the predicted mobilities are close to the observed mobilities at ionic strengths ≤0.01 M if the b-value is taken to be 4.1 Å. The predicted and observed mobilities diverge strongly at higher ionic strengths unless the b-value is reduced significantly. The results suggest that ssDNA strands exist as an ensemble of relatively compact conformations at high ionic strengths, with b-values corresponding to the relatively short phosphate-phosphate distances through space.